Suppression of CGRP and TRPV1 Expression in Dorsal Root Ganglia of Knee Osteoarthritis Rats by Huojing Decoction via TrkA/MKK3/6/p38 Pathway - Jiang X; Guo Y; Fang M; Wang X; Zhang B; Song Y; Qian J (Dove Medical Press, 2024)
Xinchao Jiang,1,* Yinyin Guo,2,* Mei Fang,1 Xin Wang,3 Biao Zhang,4 Yi Song,1 Jianxue Qian1 1Department of Pain Medicine, Suzhou Hospital of Integrated Traditional Chinese and Western Medicine, Suzhou, Jiangsu, People's Republic of China; 2Department of Oncology, Suzhou Hospital of Integrated Traditional Chinese and Western Medicine, Suzhou, Jiangsu, People's Republic of China; 3Department of Nephrology, Suzhou Hospital of Integrated Traditional Chinese and Western Medicine, Suzhou, Jiangsu, People's Republic of China; 4Department of Intensive Care, Suzhou Hospital of Integrated Traditional Chinese and Western Medicine, Suzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianxue Qian; Yi Song, Department of Pain Medicine, Suzhou Hospital of Integrated Traditional Chinese and Western Medicine, 39 Xiashatang Road, Wuzhong District, Suzhou, Jiangsu, People's Republic of China, Tel/Fax +86 0512-69388313 ; +86 0512-69388412, Email szxqjx@126.com; 376063583@qq.comObjective: Knee osteoarthritis (KOA) is a chronic condition characterized by persistent pain that can lead to severe disability. In this study, we primarily investigated the analgesic effect of Huojing decoction on MIA-induced knee arthritis.Methods: The network pharmacology method was employed to acquire target information of Huojing decoction and KOA. MIA was intratibially injected to induce KOA pain in rats. Huojing decoction was then administered once daily via intragastric administration for 14 days. Pain level was assessed by paw withdrawal threshold (PWT) and paw withdrawal latency (PWL). The levels of inflammatory cytokines were determined by ELISA and PCR. TRPV1 and CGRP were detected through immunohistochemistry. The protein expression of TrkA, MKK3/6 and p38 was assessed by Western blot.Results: Mechanical allodynia and thermal hyperalgesia were observed in KOA rats. The expression levels of inflammatory cytokines were significantly decreased after Huojing decoction infusion of KOA rats. TRPV1 and CGRP were reduced with treatment. Furthermore, the protein expressions of TrkA, MKK3/6 and p38 in the DRG of rats were significantly decreased.Conclusion: Our data suggested that Huojing decoction can alleviate inflammation in KOA pain rats. Additionally, it can inhibit the expression of TrKA, MKK3/6 and p38 signaling pathways, indicating its analgesic effect on KOA pain rats. Keywords: huojing decoction, analgesic effect, knee osteoarthritis, dorsal root ganglion, TrkA/MKK3/6/p38 pathway